2017
DOI: 10.3329/bjar.v42i1.31969
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leaf trichomes and meteorological parameters on population dynamics of aphid and jassid in cotton

Abstract: This study was conducted with CB1, CB3, CB5, CB8 and C12 cotton varieties to determine the role of leaf trichomes and meteorological factors on the abundances of aphid and jassid. The mean population of the pests on the tested varieties differed significantly and showed negative correlation with trichomes. The pests were most abundant on CB12, and each variety revealed significantly higher population of jassid than that of aphid. Both the pests built up their population in the juvenile stage of the plants (73 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…The abundance of aphid showed a significant positive correlation with the abundance of jassid on CB12, CB14 and CB15 varieties. The result conformed with that of Amin et al (2017) who reported the number of trichomes on the midrib of the cotton varieties showed significant negative correlations with the populations of aphid and jassid.…”
Section: Amin Et Al (2017) Reported Significant Variations Among Different Varieties Of Cottonsupporting
confidence: 91%
“…The abundance of aphid showed a significant positive correlation with the abundance of jassid on CB12, CB14 and CB15 varieties. The result conformed with that of Amin et al (2017) who reported the number of trichomes on the midrib of the cotton varieties showed significant negative correlations with the populations of aphid and jassid.…”
Section: Amin Et Al (2017) Reported Significant Variations Among Different Varieties Of Cottonsupporting
confidence: 91%
“…6: y = -576.01 + 7.7912x, r = 0.473, F 1, 4 = 1.2, p = 0.34) with abundance of aphid. Amin et al (2017) showed that weather parameters had insignificant effect on the population abundance of aphid on cotton plant in Bangladesh. They also reported that the aphid population started to build up at the end of October when the maximum and minimum temperatures decreased, the relative humidity slightly declined, and there was little rainfall.…”
Section: Resultsmentioning
confidence: 99%
“…The abundance and infestation of herbivore pest species vary with geographical location, climatic conditions, and host plant availability (Hidalgo et al 2013;Razdoburdin et al 2014). The host plant's growth stage, physiomorphic traits, and prevalent natural enemies also affect pest population dynamics (Amin et al 2011(Amin et al , 2015(Amin et al , 2017. Abiotic factors such as temperature, humidity, and rainfall can interrupt the growth, development, reproduction, foraging, distribution, and feeding behavior of herbivore pests, in turn impacting the frequency and intensity of pest infestations (Amin et al 2017(Amin et al , 2019.…”
Section: Thripsmentioning
confidence: 99%
“…The host plant's growth stage, physiomorphic traits, and prevalent natural enemies also affect pest population dynamics (Amin et al 2011(Amin et al , 2015(Amin et al , 2017. Abiotic factors such as temperature, humidity, and rainfall can interrupt the growth, development, reproduction, foraging, distribution, and feeding behavior of herbivore pests, in turn impacting the frequency and intensity of pest infestations (Amin et al 2017(Amin et al , 2019. Ahmed and Aslam (2000) observed that high temperatures reduced the aphid populations on rose plants.…”
Section: Thripsmentioning
confidence: 99%
See 1 more Smart Citation